High-frequency monitoring enables operational opportunities to reduce the dissolved organic carbon (DOC) load in Germany's largest drinking water reservoir. Issue 2 (3rd April 2022) - Zhan, Qing; Kong, Xiangzhen; Rinke, Karsten
ABSTRACT: Rising dissolved organic carbon (DOC) is interfering with drinking water production. While strategies for DOC removal during water treatment have been successfully implemented, the potential for DOC load reduction by optimized reservoir operation is not yet fully explored, mainly constrained by data paucity on real-time DOC dynamics. In this study, we utilized the emerging in situ high-frequency (HF) monitoring technique for DOC and developed a simulation–operation framework that promotes DOC mitigation in Germany's largest drinking water reservoir. Rappbode Reservoir is embedded in a network of smaller upstream reservoirs from which Königshütte Reservoir delivers the most water but can also be operated as a bypass system. Using high-frequency monitoring of DOC concentrations and discharge at the inflows and outflows, we constructed a mass balance model that simulated the DOC dynamics in the reservoir, allowing us to explore alternative operation regimes that deliver the same amount of water but a lower DOC load. Our results show that, through rapid decision-making that enables bypassing of water with high DOC concentrations around the drinking water reservoir, the optimized operation regime is able to reduce DOC load of the drinking water reservoir by 25 ± 3%. Therefore, our proposed operational strategy to minimize DOC loading to reservoirs is promising.